Textual linguistics on the Facebook Vote LGBT page - Gomes, Amanda Garcia [UNESP]; Candido, Gilberto Gomes; Moraes, Joao Batista Ernesto de [UNESP]; Rodrigues, Fernando de Assis (Univ Brasilia, Dept Ciencia Informacao, 2022)
This research aims to identify the characteristics of textuality present in election campaign publications published on the Social Network Online Facebook, published by the page Vote Lesbians, Gays, Bisexuals e Transgender (Vote LGBT). As for the methodological procedures, the research has an exploratory character with a qualitative approach. The investigation collected data on publications on the page of the social organization Vote LGBT that took place between September 27 and November 15, 2020, during the period of municipal elections. The results presented the analysis of five photographs published by the Vote LGBT page, based on the characteristics of textuality (intentionality, acceptability, situationality, informativeness and intertextuality) that allowed visualizing the intention of the producer and the elements that composed the publications. As conclusions, the research presented that the publications seek to inform the receiver in order to make known, publicize, disseminate, invite the debate on the guidelines that surround the community and convince the voter to vote for the Lesbian, Gay, Bisexual, Transgender, Queer, Intersex, Asexual, + (used to include other gender identities and sexual orientations that do not fit the cis-heteronormative pattern).
Keywords: Social Networks; Textual Linguistics; Textuality